The Female Target: Digitality, Psychoanalysis and the Gangbang - Semerene, Diego (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
The essay culls from classical texts and personal experiences of libertine intimacy with strangers to address age-old academic blind spots regarding group sex as a recurring fantasy and sexual practice. What is brought forth is a Freudian and Lacanian analysis of the relationship between contemporary desire and digitality through “the gangbang” as articulated on digital platforms. The focus is on digitally-assisted gangbangs involving a transvestite and several heterosexually identified males, and what such events reveal about digital media’s and heterosexuality’s demands. The author argues that this sexual configuration is a re-enactment of "the great misdeed", which Freud recounts in Totem and Taboo as the mythic primordial killing of the Father by the band of brothers. This symbolic occasion is described as the genesis of social organization and re-emerges as a form of mourning the disappearance of the fleshly body as new media turn it into digital code. Such a codification of the body awakens anxieties around the fictitious conflation between penis and phallus. In the face of the digital, man outsources his phallic power, which is suddenly required to be represented corporally at all times, to a virtually organized multitude that is willing to sacrifice freedom in the name of the group, and the legitimation of hetero-masculinity that it can presumably grant. The gangbang also appears as a digitally mediated opportunity for old fantasies of aggression and expiation to articulate themselves without putting the white male heterosexual body on the line.